Pengaruh Motivasi dan Komunikasi Terhadap Kepuasaan Kerja Serta Implikasinya Terhadap Kinerja Dosen Sekolah Tinggi Pariwisata Bandung - Sutardi, Heri (Program Studi Administrasi Bisnis, 2020)
This study intends to reveal how the performance of Bandung Tourism College lecturers (STPB) and the extent to which work motivation factors and the level of job satisfaction of lecturers and communication affect the performance of Bandung Tourism High School (STPB), while other factors that can affect the performance lecturers besides these three factors are ignored, the results are expected to contribute to the development of Human Resource management, especially management. This research uses descriptive analysis method, because this research besides wanting to get a picture of Work Motivation, Job Satisfaction, Communication and Performance of Bandung Tourism College Lecturers (STPB), also wants to get a picture of the pattern of relationships and the influence of determined research variables.